2011
DOI: 10.1158/1541-7786.mcr-10-0497
|View full text |Cite
|
Sign up to set email alerts
|

miR-200 Inhibits Lung Adenocarcinoma Cell Invasion and Metastasis by Targeting Flt1/VEGFR1

Abstract: The microRNA-200 (miR-200) family is part of a gene expression signature that predicts poor prognosis in lung cancer patients. In a mouse model of K-ras/p53-mutant lung adenocarcinoma, miR-200 levels are suppressed in metastasis-prone tumor cells, and forced miR-200 expression inhibits tumor growth and metastasis, but the miR-200 target genes that drive lung tumorigenesis have not been fully elucidated. Here, we scanned the genome for putative miR-200 binding sites and found them in the 3′-untranslated region … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
154
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(166 citation statements)
references
References 45 publications
8
154
0
4
Order By: Relevance
“…As stated earlier, miR-200b targets Ets-1 and inhibits angiogenic activity of HMECs (Chan et al, 2011). Another paper reported that miR-200b targets murine Flt-1 (Roybal et al, 2011). Down-regulation of Flt-1 by miR-200b suppressed invasion and metastasis of lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 63%
“…As stated earlier, miR-200b targets Ets-1 and inhibits angiogenic activity of HMECs (Chan et al, 2011). Another paper reported that miR-200b targets murine Flt-1 (Roybal et al, 2011). Down-regulation of Flt-1 by miR-200b suppressed invasion and metastasis of lung adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 63%
“…High expression of these three genes has been identified in non-small cell lung cancer xenografts compared with xenografts originating from other sites (5), indicating that these three factors may be significant in lung cancer progression. Indeed, VEGFA (6)(7)(8), FLT1 (9,10) and KDR (11,12) have all been demonstrated to promote lung cancer progression. However, their utility as prognostic markers remains unknown owing to the conflicting findings of previous studies (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The findings argue that the activated receptor such as VEGF plays a role as an antigenic factor and that VEGFR‐2 is necessary for tumor metastasis 46. Western blot bands demonstrated a decrease in phosphorylation of VEGFR‐2 after treatment with SiO 2 @LDH‐VP16 on A549 cells.…”
Section: Discussionmentioning
confidence: 94%